PUBLIC MANAGERS' PERCEPTION OF THE PERFORMANCE MEASUREMENT SYSTEM, WITH EMPHASIS ON THE PERFORMANCE PRISM - Monteiro, Otávio Henrique Cintra (Management Control Review, 2020)
Performance measurement system is an instrument that supports better organizational performance. This theme has evolved over time, while systems have become multidimensional and intent on projecting the future. In addition, in an open system logic, the understanding of the stakeholders becomes relevant to a performance measurement system. For this reason, the system model called Prism de Performance draws attention because it is based on stakeholders. Therefore, this article aims to analyze the perception of public managers who work in the implementation of strategic planning and performance on performance measurement systems, with an emphasis on the Performance Prism. Through a questionnaire data were obtained and analyzed using the Kruskal-Wallis statistical model. As a result, it was found that the focus on stakeholders is considered important for a dimension of a performance measurement system and that the Performance Prism is not known by professionals who work with the implementation of strategic planning and monitoring of results, even though the model is applicable to non-profit entities.